Nothofagus pumilio and N. antarctica: The Most Widely Distributed and Cold-Tolerant Southern Beeches in Patagonia - Soliani, Carolina; Marchelli, Paula; Mondino, Victor Alejandro; Pastorino, Mario Juan; Mattera, María Gabriela; Gallo, Leonardo Ariel; Aparicio, Alejandro Gabriel; Torres, Ana Delia; Tejera, Eduardo; Schinelli Casares, Teresa (Springer, 2021)
Nothofagus pumilio (Poepp. & Endl.) Krasser, known as lenga, and Nothofagus antarctica (G. Forster) Oerster, commonly called ñire, are tree species of the temperate forests of southern South America, occurring in temperate-rainy forest districts, in the subalpine transition area, and in poorly drained sites (Veblen et al. 1996). Their natural distributions in Chile and Argentina mainly correspond to the Cordillera de los Andes, from 36° S to the south of Tierra del Fuego archipelago (55° S). In Chile, N. pumilio also inhabits the Coastal Range (Cordillera de Nahuelbuta) where it grows associated with Araucaria araucana forests above 1400 m asl. In turn, N. antarctica is distributed in the Central Depression of Chile, from Valdivia toward austral latitudes. Throughout their entire distribution in Argentina, lenga and ñire forests co-occur and overlap to a greater or lesser extent. This shared geographical distribution covers approximately 18° of latitude (2200 km of extension) and is the widest among the South American Nothofagus. Recently, the national forest inventory of Argentina (CIEFAP and MAyDS 2016) revealed a total of 1,595,661 ha and 864,148 ha of lenga and ñire forests, respectively. The National Park Administration of Argentina protects a portion of all this forest surface (34% and 15%, respectively), belonging the rest to provincial jurisdictions. Estación Experimental Agropecuaria Bariloche Fil: Soliani, Carolina. Instituto Nacional de Tecnología Agropecuaria (INTA). Estación Experimental Agropecuaria Bariloche; Argentina Fil: Soliani, Carolina. Consejo Nacional de Investigaciones Cientificas y Tecnicas. Instituto de Investigaciones Forestales y Agropecuarias Bariloche; Argentina Fil: Marchelli, Paula. Instituto Nacional de Tecnología Agropecuaria (INTA). Estación Experimental Agropecuaria Bariloche; Argentina Fil: Easdale, Marcos Horacio. Consejo Nacional de Investigaciones Cientificas y Tecnicas. Instituto de Investigaciones Forestales y Agropecuarias Bariloche; Argentina Fil: ...